La modernité baudelairienne et son impact sur la pensée et la poésie d’Ilyās Abu Šabaka - Khudhur, Abbas Krimich (Al-Adab Journal, 2021)
This study reveals a clear and profound influence of Baudelaire’s poetics, philosophy and thought on the literary production of the Lebanese poet and the avant-garde of modern Arabic poetry Ilyās Abu Šabaka (1903 - 1947). Abu Šabaka’s poetic texts evoke part of what the read of Baudelaire’s poetry, but he did not resort to the method of dialogue in his relations with the texts. It is due to the fact that the two poets have the same perception towards the universe and the life, based on two opposites: the hatred of the life on the one hand and the inclination and the passion for it until the ecstasy on the other hand. The study therefore deals with the question of influence and effect among poets, intellectual dualism, the presence of the absent text and cultural beauty.